Mitochondrial regulation of cell cycle and proliferation - Antico Arciuch, Valeria Gabriela (2012)
Eukaryotic mitochondria resulted from symbiotic incorporation of α-proteobacteria into ancient archaea species. During evolution, mitochondria lost most of the prokaryotic bacterial genes and only conserved a small fraction including those encoding 13 proteins of the respiratory chain. In this process, many functions were transferred to the host cells, but mitochondria gained a central role in the regulation of cell proliferation and apoptosis, and in the modulation of metabolism; accordingly, defective organelles contribute to cell transformation and cancer, diabetes, and neurodegenerative diseases. Most cell and transcriptional effects of mitochondria depend on the modulation of respiratory rate and on the production of hydrogen peroxide released into the cytosol. The mitochondrial oxidative rate has to remain depressed for cell proliferation; even in the presence of O 2, energy is preferentially obtained from increased glycolysis (Warburg effect). In response to stress signals, traffic of pro-and antiapoptotic mitochondrial proteins in the intermembrane space (B-cell lymphoma-extra large, Bcl-2-associated death promoter, Bcl-2 associated X-protein and cytochrome c) is modulated by the redox condition determined by mitochondrial O 2 utilization and mitochondrial nitric oxide metabolism. In this article, we highlight the traffic of the different canonical signaling pathways to mitochondria and the contributions of organelles to redox regulation of kinases. Finally, we analyze the dynamics of the mitochondrial population in cell cycle and apoptosis. Antioxid. Redox Signal.